MANAJEMEN KEPALA MADRASAH DALAM PENINGKATAN MUTU PENDIDIKAN - Tanjung, Zulkifli; Abdurrahim, Abdurrahim; Handoko, Handoko (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The management and leadership of the principal is an important factor that determines the improvement of the quality of education in every school. All program design and implementation, as well as mobilizing people to work both educators and education staff within the framework of quality improvement. Improving services that provide satisfaction to students, teachers and employees must be the focus of the principal. So that the interaction between internal and external components is expected to give birth to performance and achievements that have an impact on graduates as school outputs that provide customer satisfaction. This paper aims to explain how important the role of the principal and the improvement of the quality of education in every school is.